Assessment of Growth and Productivity of Zinnia (Zinnia Elegans) Against Exogenous Application of NPK and Boron (Journal of Agriculture and Biology, 2025)
Study was conducted to evaluate the effects of varying concentrations of macronutrients (NPK) and micronutrients (boron) on the growth and flowering of “Zinnia elegans” cv. Zinnia Binary’s Giant under the subtropical climate of Lahore. The study was comprised ten treatments with four replications, including a control with different combination of boron and NPK applications. Seeds of “Zinnia Benary’s Giant” were sown in germination tray having substrate of leaf manure, sand, and silt, and transplanted into 12-inch earthen pots at the age of 20 days. Foliar applications of nutrients were started 25 days after transplanting. Data regarding following parameters were recorded such as days to flowering, fresh and dry weight of plant and flower, plant height, root length, flower diameter, leaf area and chlorophyll content, proline content, superoxide dismutase, catalase, peroxidase and total phenolics using standardized measurement techniques. After statistical analysis, results indicated that 50 ppm boron significantly reduced the time to flower opening to 55.75 days, while NPK applications generally delayed flowering. The optimal combination of 50 ppm boron and 2g NPK resulted in maximum, plant fresh weight (32.4 g), and dry weight (7.575 g), root length (33.325 cm), shoot length (57 cm) than control showed smallest shoot length (22.125cm), root length (10.125cm), pant fresh weight (13.175g) and dry weight (2.7g). Flower diameter peaked at 8.5225 cm with this treatment. Notably, chlorophyll content reached 5.002 mg/g FW, while peroxidase (POD) and superoxide dismutase (SOD) and activities, indicators of plant stress response, were highest with the combined nutrient application. In contrast, higher boron concentrations (100 ppm) suppressed growth and enzyme activity. Generally, the outcomes suggest that the synergistic application of 50 ppm boron and 2g NPK significantly enhances the growth and flowering of “Zinnia elegans”, emphasizing importance of optimal nutrient management in improving floral crop production in Pakistan’s burgeoning floriculture sector.